TOI-257b (HD 19916b): a warm sub-saturn orbiting an evolved F-type star. Issue 3 (28th December 2020) - Addison, Brett C; Wright, Duncan J; Nicholson, Belinda A; Cale, Bryson; Mocnik, Teo; Huber, Daniel; Plavchan, Peter; Wittenmyer, Robert A; Vanderburg, Andrew; Chaplin, William J; Chontos, Ashley; Clark, Jake T; et al.
ABSTRACT: We report the discovery of a warm sub-Saturn, TOI-257b (HD 19916b), based on data from NASA's Transiting Exoplanet Survey Satellite ( TESS ). The transit signal was detected by TESS and confirmed to be of planetary origin based on radial velocity observations. An analysis of the TESS photometry, the Minerva -Australis, FEROS, and HARPS radial velocities, and the asteroseismic data of the stellar oscillations reveals that TOI-257b has a mass of MP = 0.138 ± 0.023 M_J (43.9 ± 7.3 M_ ), a radius of RP = 0.639 ± 0.013 R_J (7.16 ± 0.15 R_ ), bulk density of 0.65^+0.12_-0.11 (cgs), and period 18.38818^+0.00085_-0.00084 days . TOI-257b orbits a bright (V = 7.612 mag) somewhat evolved late F-type star with M * = 1.390 ± 0.046 M_sun, R * = 1.888 ± 0.033 R_sun, T eff = 6075 ± 90 K, and v sin i = 11.3 ± 0.5 km s −1 . Additionally, we find hints for a second non-transiting sub-Saturn mass planet on a ∼71 day orbit using the radial velocity data. This system joins the ranks of a small number of exoplanet host stars (∼100) that have been characterized with asteroseismology. Warm sub-Saturns are rare in the known sample of exoplanets, and thus the discovery of TOI-257b is important in the context of future work studying the formation and migration history of similar planetary systems.